2022
DOI: 10.1001/jamapediatrics.2022.0008
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Early Intervention Services Before Age 3 Years and Performance on Third-Grade Standardized Tests Among Children Exposed to Lead

Abstract: IMPORTANCEResearch has shown that early intervention programs can improve academic outcomes of children with developmental delays. It has been suggested that similar programs may combat the deleterious effects of lead on children's neurodevelopment. However, to our knowledge, there are no published studies examining this possibility.OBJECTIVE The objective of this study was to estimate the association between receipt of early intervention services and third-grade standardized test scores among children exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…EI is a federal program aimed at reducing developmental delay in at‐risk infants and toddlers (New York State Department of Health, 2023). A study conducted in New York City enrolled any child with a lead level of 4 mcg/dL or greater into EI (Stingone et al., 2022). Children who received the services ( n = 2757), compared with children who did not ( n = 8160) were 14% (95% CI, 9%–19%) and 16% (95% CI, 9%–23%) more likely to score at or above grade level in math and English‐language arts on standardized 3rd grade exams.…”
Section: Care and Public Policymentioning
confidence: 99%
“…EI is a federal program aimed at reducing developmental delay in at‐risk infants and toddlers (New York State Department of Health, 2023). A study conducted in New York City enrolled any child with a lead level of 4 mcg/dL or greater into EI (Stingone et al., 2022). Children who received the services ( n = 2757), compared with children who did not ( n = 8160) were 14% (95% CI, 9%–19%) and 16% (95% CI, 9%–23%) more likely to score at or above grade level in math and English‐language arts on standardized 3rd grade exams.…”
Section: Care and Public Policymentioning
confidence: 99%
“…Though these secondary prevention efforts were widely accepted as the right path forward to provide support for Flint families, research has been lacking on the efficacy of therapy and education programs, such as EI, for children with a history of lead exposure. The study by Stingone et al 4 is the first to prove the benefits of such intervention and bolsters the foundation for a new national gold standard for serving children and families who continue to be poisoned by lead because of decades of insufficient primary prevention strategies.…”
Section: Promise Of Early Intervention For Children Exposed To Leadmentioning
confidence: 99%
“…2 Subsequent advances in the method allowed high-resolution karyotype analysis and extended the utility to even small regions of the chromosome being deleted, duplicated, or rearranged. 3 This was followed in the late 20th century by application of diagnosisrelated tests based on fluorescence in situ hybridization 4 or other specific assays, and now we have such tools as seizure panels. 5 Microarray has also been an important contributor but with the introduction of whole-exome sequencing and even wholegenome sequencing, it is clear that up to one-third of disorders in the newborn period may be missed without the more comprehensive testing.…”
Section: Related Article Page 478mentioning
confidence: 99%
“…Specialized early intervention (EI) services for young children may also be more successful when families trust and feel supported by their providers, reflecting relational health between families and providers (Jimenez et al., 2012 ; Miller, Stein et al., 2022 ). A recent analysis found that EI services, which entail individualized service plans tailored to child and family needs, mitigated the impact of lead exposure on later math and reading scores (Stingone et al., 2022 ). Thus, in addition to identifying and eliminating the physical sources of environmental exposures when possible (e.g., as with the Flint Water Crisis), providing individual, developmentally‐tailored interventions—including those that address relational health across CSE contexts during early childhood—may be promising strategies for addressing impacts of exposure.…”
Section: Developmentally‐informed Intervention Considerations: Period...mentioning
confidence: 99%